On the incidence graph of circular spaces - Sorgun, Sezer; Ertaş, Ali Gökhan; Günaltılı, İbrahim (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2024)
A configuration of the triple (P,L,I) is an incidence relation which has the properties